The Sound of Ions: Acoustic Detection of High-Energy Beams. (2nd January 2020) - Assmann, Walter; Parodi, Katia
Abstract : Acoustic effects of ions have been well known for many years and working at CERN one may have noticed the big "bang" when the Large Hadron Collider beam is finally damped into a block of graphite. Acoustic detection of ions ("ionoacoustics") belongs to the more general thermoacoustic effect, where a medium is locally heated by instantaneous energy deposition and the following adiabatic expansion creates an acoustic shock wave. This effect is widely used in optoacoustics for biomedical imaging. Here, pressure waves are induced by the local, often artificially enhanced absorption of light in tissue [1 ]. First ideas to detect ionizing particles by their sound generated in liquids were published by Askaryan [2 ] and seminal experimental studies by Sulak et al. [3 ], very soon considered for cosmic neutrino detection due to thereby affordable large detector arrays [4 ].